Evaluation of the Causes of Resistant Hypertension in Non-dialysis Chronic Kidney Disease Patients - Haque, Md Enamul; Saqeb, Khan Md Nazmus (Bangladesh Critical Care Journal, 2022)
Background: In Chronic Kidney disease (CKD), resistant hypertension (RH) is a common condition due to a combination of factors including sodium retention, increased activity of the renin-angiotensin system, and enhanced activity of the sympathetic nervous system. The aim of the study was to determine the causes of resistant hypertension in non-dialysis Chronic Kidney Disease Patients. Methods: This descriptive cross-sectional study was conducted in the department of Nephrology & Internal Medicine of Dhaka Medical College Hospital from 18th January 2016 to 20th may 2016. Patients aged above 18 years admitted with resistant RH and CKD were enrolled in the study after fulfilling the inclusion and exclusion criteria. The study involved 50 CKD patients who had RH. Purposive consecutive type of sampling technique was applied for sample collection. Detail socio-demographic data were collected and recorded in a predesigned questionnaire. Clinical examination and relevant investigations were done. Data was analysed with SPSS version 22.0. P value of <0.05 was considered significant. Result: Maximum number of patients 23(46.0%) were between 46-60 years age group, mean age of the patient was 53.17 ± 8.42 years. Male: female ratio was 1.63:1. Study showed that frequency of RH and CKD gradually increased with age. In case of both sexes, 46-60 years age group showed the highest incidence for CKD. The mean systolic and diastolic blood pressures (BP) were 133.04 ± 12.91 mmHg and 81.07 ± 6.41 mmHg respectively. Those with diabetes mellitus, obesity (BMI > 27.5 kg/m2) and those who were older than 55 years were significantly higher in the RHT group than in the non-RHT group. Conclusion: RH in CKD patients was significantly associated with the presence of obesity, diabetes mellitus and increased age. These factors should always be kept in mind while treating HTN in CKD patients. Bangladesh Crit Care J March 2022; 10 (1): 19-25